IMPLEMENTASI FORWARD CHAINING UNTUK DIAGNOSA DEFISIENSI VITAMIN LARUT DALAM LEMAK BERBASISKAN WEB - Nina Sevani; Melvin Joshua (Jurnal Informatika, 2015)
The growth of information technology is increasing lately. People can get the actual information from websites. The combination between website and expert system will help people to make an application that can think like an expert and spread it all around the world using the internet. The technology can be used to solve the availability problem of expert nutrient in Indonesia. The application was developed using forward chaining method as the inference system. It will make the application work like a nutrient expert, which asks the patient from general to specified symptoms. The knowledge based of the application was collected from trusted resources like nutrient experts and nutrient books. The application was tested by the nutrient expert. The result shows that the application can work properly like an expert.